A histopathological study of liver and biliary remnants with clinical outcome in cases of extrahepatic biliary atresia - Roy Paromita; Chatterjee Uttara; Ganguli M; Banerjee Sugato; Chatterjee S; Basu A (Wolters Kluwer Medknow Publications, 2010)
Context: The indicators of poor prognosis in cases of extrahepatic biliary atresia (EHBA) continue to remain controversial. Aims: To correlate the histopathological findings of wedge biopsy from liver and tissue obtained from the shaving at the porta hepatis, during hepatic portoenterostomy, with the clinical outcome. Materials and Methods: All cases of EHBA surgically treated in our hospital from 1995 to 2006 have been reviewed. Wedge biopsies of the liver and biopsies from the porta hepatis were analyzed with hemotoxylin-eosin stains and immunohistochemistry. The parameters correlated with clinical outcomes were - presence of large bile ducts ( > 150μm diameter) in the portal tissue plaque, degree of fibrosis (semi-quantitative; graded as mild, moderate and severe), presence of ductal plate malformation (DPM) and age at operation. Results: The proportions of patients with small or large ductal diameter who remained clinically controlled (serum bilirubin < 1.5mg/dl with no evidence of end stage liver failure) were 39% and 66.6% respectively (P=0.44). There was a highly significant correlation between the extent of fibrosis and clinical outcome. Mild, moderate and severe fibrosis resulted in clinical control rates of 78.5%, 34.4% and 24% respectively (P=0.001). Ductal plate malformation was seen in 15% of our cases and was uniformly associated with poor outcome. A non-significant trend towards poorer outcome was seen with increasing age at surgery. Conclusions: Histopathological correl ations with clinical outcome in EHBA have been rarely reported from the Indian subcontinent. A greater degree of fibrosis at the time of hepatic portoenterostomy and presence of ductal plate malformation is associated with a significantly poorer clinical outcome.